ANTIOXIDANT ACTIVITY OF ETHYL ACETATE FRACTION OF MACARANGA TRILOBA LEAVES FROM CENTRAL KALIMANTAN - Ardhany, Syahrida Dian; Mulia, Dewi Sari; Rosawanti, Pienyani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Macaranga triloba was used by the local for diabetes, antidiabetes have strong relation with antioxidant activity, antioxidants have been shown to prevent the destruction of Î²-cells by inhibiting the preoxidation chain reaction, plants containing natural antioxidant (like flavonoid and alkaloid) can protect Î² cell function. So the objective of this study is to investigate antioxidant activity of ethyl acetate fraction of Macaranga triloba leaves and did preliminary phytochemical screening (Alkaloid and Flavonoid). Methods: Macaranga triloba leaves (Mahang damar) were collected from the local areas of Bukit Rawi Central Kalimantan. Macaranga triloba leaves were extracted using maceration methods, followed by fractionation using liquid-liquid extraction methods starting from n-hexane, ethyl acetate, methanol but in this research used ethyl acetate fraction of Macaraga triloba and preliminary phytochemical screening for alkaloid used dragendorff and flavonoid used Pb Acetate. Antioxidant activity test was carried out using 1,1-diphenyl-2-pikrilhidrazil (DPPH) with quercetin as a reference. Results: It was found that ethyl acetate fraction of Macaranga triloba leaves containing positive flavonoid that has been shown by dragendorff methode (brick red sedimen) and positive alkaloid by Pb acetate. The inhibition concentration 50 (IC50) value of ethyl acetate fraction of Macaranga triloba leaves is 56.93 ppm Conclusion: Macaranga triloba leaves by preliminary screening of phytochemical containing alkaloid and flavonoid. Antioxidant activity of ethyl acetate fraction with IC50 = 56.93 ppm is weaker than quercetin (IC50 = 4.46 ppm), but still in range value of strong antioxidant activity (50-100 ppm)